Network Capacity Issues in Joint Buffer Management and Scheduling (JoBS) - Nur Idawati Md Enzai; Hasnorhafiza Husni; Siti Sara Rais; Nor Raihan Zulkefly (MECS, Modern Education & Computer Science Press, 2024)
Joint Buffer Management and Scheduling (JoBS) algorithm is known for its services in providing loss and delay differentiation independently at each node. Though JoBS have encompassed the main network parameters, another crucial element with respect to network performance namely capacity or bandwidth has not been addressed in term of its limitation. This paper aims to provide the fundamental idea of incorporating bandwidth constraints provisioning in addition to the existing constraints. This proposal is expected to be realized through simulation studies in upcoming work.